2020
DOI: 10.1130/abs/2020am-356372
|View full text |Cite
|
Sign up to set email alerts
|

Uv-B Radiation Was the Devonian-Carboniferous Boundary Terrestrial Extinction Kill Mechanism

Abstract: There is an unexplained terrestrial mass extinction at the Devonian-Carboniferous boundary (359 million years ago). The discovery in east Greenland of malformed land plant spores demonstrates that the extinction was coincident with elevated UV-B radiation demonstrating ozone layer reduction. Mercury data through the extinction level prove that, unlike other mass extinctions, there were no planetary scale volcanic eruptions. Importantly, the Devonian-Carboniferous boundary terrestrial mass extinction was coinci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 9 publications
0
27
0
Order By: Relevance
“…A prominent environmental stressor is UV radiation, which has been associated to some extinctions as in the Devonian–Carboniferous boundary period (Marshall et al., 2020). Nowadays, UV radiation has been intensified with human‐induced environmental changes due to, among other factors, the depletion of the ozone layer (Caldwell & Flint, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…A prominent environmental stressor is UV radiation, which has been associated to some extinctions as in the Devonian–Carboniferous boundary period (Marshall et al., 2020). Nowadays, UV radiation has been intensified with human‐induced environmental changes due to, among other factors, the depletion of the ozone layer (Caldwell & Flint, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the volcanic "smoking gun" as a potential trigger of the Hangenberg Crisis has been questioned 8 . According to 8 , elevated UV-B radiation and a drastic drop in stratospheric ozone during global warming were responsible for this biotic overturn. Moreover, Fields et al 52 , postulated supernova explosions as a trigger for the event.…”
Section: Discussionmentioning
confidence: 99%
“…Marshall et al 8 described floral malformations in east Greenland and interpreted the observed floral mutagenesis to be a result of elevated UV-B radiation, reflecting ozone-layer reduction that was suggested to have been associated with global warming. Surprisingly, according to those authors, mercury data excluded planetary-scale volcanism as a potential trigger for the end-Devonian Hangenberg Crisis.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is also possible that the field during the Devonian directly enabled biological crises through depletion of the ozone layer, which allowed more UV-B radiation to reach Earth's surface. Although it would be expected that malformed spores would be more widespread, and associated with other parts of the Devonian, instead of in distinctive intervals as the study of Marshall et al (2020) suggests.…”
Section: Did the Field Have An Impact On Life In The Devonian?mentioning
confidence: 98%
“…Recently, the study of Marshall et al (2020) has linked the terrestrial phase of the Hangenberg event at the Devonian-Carboniferous boundary to an increase in ultraviolet (specifically, UV-B) radiation, which they hypothesize to be caused by an increase in convective transport of ClO (chlorine monoxide) through global warming. Fields et al (2020) dispute this cause and have instead suggested that the increase in UV-B radiation during the Hangenberg event could have been caused by supernovae.…”
Section: Did the Field Have An Impact On Life In The Devonian?mentioning
confidence: 99%